2007
DOI: 10.1007/s11219-006-9009-9
|View full text |Cite
|
Sign up to set email alerts
|

A method to elicit architecturally sensitive usability requirements: its integration into a software development process

Abstract: In the Human-Computer Interaction (HCI) community, software usability has primarily been concerned with the presentation of information, more precisely with the user interface. However, some usability problems can prove costly to fix if the changes require modifications that reach beyond the presentation layer, namely those that cannot be easily accommodated by the software architecture. Taking into account some usability requirements earlier in the software development cycle, specifically prior to the archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…It was proven that learnability is positively correlated with usability (Alves & Nunes, 2016). Rafla et al (2007) revealed that in the Human-Computer Interaction (HCI) community, the presentation of information is the primary concern of software usability. Presentation is about the user interface's layout (Rafla et al, 2007;Kumar et al, 2015).…”
Section: Research Modelmentioning
confidence: 99%
“…It was proven that learnability is positively correlated with usability (Alves & Nunes, 2016). Rafla et al (2007) revealed that in the Human-Computer Interaction (HCI) community, the presentation of information is the primary concern of software usability. Presentation is about the user interface's layout (Rafla et al, 2007;Kumar et al, 2015).…”
Section: Research Modelmentioning
confidence: 99%
“…Finally, Rafla et al [28] propose the Usability managed Quality Attributes Workshop with the aim of discovering and documenting usability requirements using the usability properties of Folmer [31] and the scenarios of Bass [32] as guidelines. Users are expected to identify those requirements that are relevant to the software.…”
Section: Usability Requirements Focused Proposalsmentioning
confidence: 99%
“… Domain-oriented processes, such as Web applications or mobile devices [17,19,26]  Agile methods [15,23,25,30].  The last category consists of proposals that have an impact on the usability requirements specification [14,16,22,24,28].…”
mentioning
confidence: 99%
“…Juristo et al [65] and Rafla et al [99] deal with the implications of applying usability techniques during the requirements phase, and note the resulting problems and impact on the development.…”
Section: Chapter 3 Integrating User-centered Design Into Agile Softwmentioning
confidence: 99%